Understanding the root of attack in android malware - Rahiwan Nazar, Romli; Mohamad Fadli, Zolkipli; Al-Ma’arif, Ahmad; Muhammed Ramiza, Ramli; Mohamad Aizi, Salamat (Penerbit UTHM, 2018)
With the rapid pace of development and change in mobile device technology and Android versions, Android malware has emerged and become a focus in current research. Subsequently, security and privacy have become one of the main issues in android malware. Therefore, it is essential to understand the behavior of Android malware in order to conceive an effective technique in malware detection and analysis. This article presents a comprehensive study regarding Android platform, its features in android malware code and also discusses the result from previous studies in order to support forward-looking in Android study.